2019
DOI: 10.1177/0163443719846612
|View full text |Cite
|
Sign up to set email alerts
|

‘That’s not necessarily for them’: LGBTIQ+ young people, social media platform affordances and identity curation

Abstract: Lesbian, gay, bisexual, transgender, queer, intersex, and other non-heterosexual and gender diverse (LGBTIQ+) young people utilise a range of digital media platforms to explore identity, find support and manage boundaries. Less well understood, however, is how they navigate risk and rewards across the different social media platforms that are part of their everyday lives. In this study, we draw on the concept of affordances, as well as recent work on curation, to examine 23 in-depth interviews with LGBTIQ+ you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 34 publications
6
112
0
5
Order By: Relevance
“…My participants were also aware of the performative and selective nature of the self that is generated online or through app use. Previous research on social media and identity has highlighted that people carefully curate their online identities, choosing what image of themselves they would like others to see, while recognising that this is at best only a partial view (Hanckel et al, 2019). For many social media users, this selective performance of selfhood incorporates the awareness that social media platforms present ‘public’ versions of selves, and that details about oneself that are considered ‘private’ or inappropriate for public exposure are not typically revealed on the platforms (Pitcan et al, 2018; Sujon, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…My participants were also aware of the performative and selective nature of the self that is generated online or through app use. Previous research on social media and identity has highlighted that people carefully curate their online identities, choosing what image of themselves they would like others to see, while recognising that this is at best only a partial view (Hanckel et al, 2019). For many social media users, this selective performance of selfhood incorporates the awareness that social media platforms present ‘public’ versions of selves, and that details about oneself that are considered ‘private’ or inappropriate for public exposure are not typically revealed on the platforms (Pitcan et al, 2018; Sujon, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an existing scale to assess how LGBTQ+ youth use social media in positive ways, scale items were developed through a literature review, interviews with LGBTQ+ youth (Craig et al, 2015;, and consultation with a youth advisory board consisting of LGBTQ+ youth from the United States and Canada. Items such as feeling connected and helping others emerged primarily from the literature (Hanckel et al, 2019), whereas "figuring out where I fit" and "sharing my story" came from the authors' qualitative work with…”
Section: Methodsmentioning
confidence: 99%
“…Yet, current research does not identify the particular motivations and benefits afforded to LGBTQ+ youth via social media participation. Given research indicating that social media provides a breadth of important opportunities and positive impacts for many LGBTQ+ youth (Craig & McInroy, 2014;Hanckel et al, 2019), this study sought to explore more specifically the benefits of social media for this population and develop a Social Media Benefits Scale (SMBS).…”
Section: A Social Media Benefits Scalementioning
confidence: 99%
“…Privacy calculus happens on Trans Time when people disclose personal information (e.g., personal details of gender transition) in exchange for social support and community. DeVito et al [23] and Hanckel et al [41] found that LGBTQ+ people manage boundaries meticulously on social media sites to mitigate risk related to their LGBTQ+ identities, as a way to deal with marginalization and stigma. Haimson et al [36] detailed how trans people manage privacy and disclosure on social media via digital footprints related to past identities, such as by editing content, partitioning networks, and maintaining multiple accounts.…”
Section: Privacy and Audiencementioning
confidence: 99%